2013
DOI: 10.1093/jxb/ert142
|View full text |Cite
|
Sign up to set email alerts
|

High temperature stress and its effect on pollen development and morphological components of harvest index in the C3 model grass Brachypodium distachyon

Abstract: The effect of high temperatures on harvest index (HI) and morphological components that contribute to HI was investigated in two lines (Bd21 and Bd21-3) of Brachypodium distachyon, a C3 grass recognized as a tractable plant, to address critical issues associated with enhancing cereal crop yields in the presence of global climate change. The results demonstrated that temperatures ≥32 °C eliminated HI. Reductions in yield at 32 °C were due primarily to declines in pollen viability, retention of pollen in anthers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 54 publications
3
65
0
1
Order By: Relevance
“…This is further corroborated by two studies in which more negative effects on reproductive success were found if heat was applied to the male than to the female parental plants of a cross (Levy et al 1978;Peet et al 1998). Similar conclusions were drawn for other plant species, such as bean, cowpea, groundnut, brachypodium, barley and rice (Ahmed et al 1992;Prasad et al 1999;Suzuki et al 2000;Sakata et al 2000;Harsant et al 2013). The contrasting cultivars identified here may be used to dissect the physiological basis for pollen heat sensitivity.…”
Section: Pollen Viability Limits Fruit Set Under Ltmh Conditionssupporting
confidence: 84%
“…This is further corroborated by two studies in which more negative effects on reproductive success were found if heat was applied to the male than to the female parental plants of a cross (Levy et al 1978;Peet et al 1998). Similar conclusions were drawn for other plant species, such as bean, cowpea, groundnut, brachypodium, barley and rice (Ahmed et al 1992;Prasad et al 1999;Suzuki et al 2000;Sakata et al 2000;Harsant et al 2013). The contrasting cultivars identified here may be used to dissect the physiological basis for pollen heat sensitivity.…”
Section: Pollen Viability Limits Fruit Set Under Ltmh Conditionssupporting
confidence: 84%
“…The microspore cytoplasm contains variable amounts of insoluble polysaccharides and proteins at different developmental stages. Anther wall development follows the monocotyledonous-type, which is composed of an epidermal layer, an endothecial layer, one middle layer and a secretorytype tapetum (Harsant et al 2013;Sharma et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that hightemperature stress may result in a mixed population of both dead and perfectly viable pollen within the same anther locule has recently been explained with a model where initially small differences between microspores in metabolic performance or developmental progression are amplified by competition for nutrients in the locular fluid (Carrizo García et al, 2017). Notably, pollen injury is often accompanied by aberrations in tapetum development (hypertrophy) or morphology and alterations in the timing of tapetum degeneration (Iwahori, 1965;Saini et al, 1984;Ahmed et al, 1992;Kim et al, 2001;Suzuki et al, 2001;Abiko et al, 2005;Oshino et al, 2007;Djanaguiraman et al, 2013;Harsant et al, 2013).…”
mentioning
confidence: 99%